A possible genealogy of decolonial bodies: the sino-latin american work of Zairong Xiang (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
The recent translation of the book Queer Ancient Ways, a decolonial exploration by Zairong Xiang has activated for us new teaching and curatorial practices based on what he himself calls cosmopolitism. By collecting a complex cultural diversity from a variety of sources; his work calls into question the "origins" of queer culture in England and in the United States, which enabled us to detect translation as a colonial device of worlds and bodies, a persistent symptom of the extractivism of subjectivities promoted by the various ways of colonizing and embodying power relations.
Keywords: queer paths; translation; decolonial practices; cosmopolitanism; transdualism